CTNI-19. PHASE I TRIAL OF DAY101 IN PEDIATRIC PATIENTS WITH RADIOGRAPHICALLY RECURRENT OR PROGRESSIVE LOW-GRADE GLIOMA (LGG). (9th November 2020) - Wright, Karen; Krzykwa, Emily; Greenspan, Lianne; Chi, Susan; Yeo, Kee Kiat; Prados, Michael; Mueller, Sabine; Haas-Kogan, Daphne
Abstract: BACKGROUND: We report phase I data examining pharmacokinetics, safety and preliminary efficacy of the dimeric, pan-RAF inhibitor DAY101 (formerly TAK-580/MLN2480) in pediatric patients with radiographically recurrent/progressive LGGs harboring MEK/ERK pathway alterations. METHODS: Oral DAY101 was administered weekly to patients < 18 years of age with radiographically recurrent/progressive LGG for 4-week cycles up to a maximum of 2 years. The starting DAY101 dosage was 280 mg/m 2 . Dose limiting toxicities were determined after one cycle. RESULTS: We treated nine eligible patients at 280, 350, and 420 mg/m 2 . Seven patients had KIAA1549:BRAF fusions, one a novel SRGAP3-RAF1 gene fusion and one with NF1 mutation. PK parameters following weekly administration of DAY101 in children mirrored the adult data, with dose-proportional increases in Cmax and AUC observed. There were no DLTs. The most common toxicity was skin rash followed by achromotrichia and nevi formation. There was only one grade 3 elevation is CPK and no grade 4 adverse events. A 2.2-fold mg/kg exposure difference was observed with respect to weight-based dosing and suggested a correlation to independent, centrally reviewed best radiographic RANO responses of 2 complete responses, 2 partial responses, 3 stable disease, and 2 progressive disease. Median time to response was 10.5 weeks (range: 8–32 weeks). CONCLUSIONS: These phase 1 data provide initial pharmacokinetic parameters outlining oral weekly dosing of DAY101 in pediatric patients with radiographically recurrent and progressive LGG. Plasma exposures of DAY101 are similar in children and adults. Oral weekly DAY101 is well-tolerated and shows anti-tumor activity. The amended protocol explores differential dosing to achieve similar responses across a variety of body surface areas.